Usefulness of Individualized Homoeopathic Medicine in Androgenetic Alopecia – An Evidence Based Case Series (Advancements in Homeopathic Research, 2024)
Introduction: Androgenetic alopecia is the most  common form of hair loss. It is also referred to as male  pattern hair loss and female pattern hair loss. It affects  more commonly men than women. Conventional  management involves the use of minoxidil, which is  also having side effects. Case summary: Four cases of androgenetic alopecia  successfully treated with homoeopathic treatment are  reported here. The first, second, third case showed  improvement with Phosphorus, fourth case showed  improvement with Natrum muriaticum. All four  cases were treated with individualised homoeopathic  medicine. All these cases were followed up regularly  and they showed significant improvement. In each  case, the causal attribution to the prescribed medicine  was established by the Modified Naranjo Criteria  Score. This evidenced-based case series suggests that  androgenetic alopecia can be successfully managed  with individualised homoeopathic treatment.
Keywords: Androgenetic Alopecia; Constitutional Homoeopathic Medicine; Modified Naranjo Criteria; Natrum muriaticum; Phosphorus; Skin